The role of SIRT6 protein in aging and reprogramming of human induced pluripotent stem cells - Sharma, Amit; Diecke, Sebastian; Zhang, Wendy Y; Lan, Feng; He, Chunjiang; Mordwinkin, Nicholas M; Chua, Katrin F; Wu, Joseph C (The Journal of biological chemistry, 2013)
Aging is known to be the single most important risk factor for multiple diseases. Sirtuin 6, or SIRT6, has recently been identified as a critical regulator of transcription, genome stability, telomere integrity, DNA repair, and metabolic homeostasis. A knockout mouse model of SIRT6 has displayed dramatic phenotypes of accelerated aging. In keeping with its role in aging, we demonstrated that human dermal fibroblasts (HDFs) from older human subjects were more resistant to reprogramming by classic Yamanaka factors than those from younger human subjects, but the addition of SIRT6 during reprogramming improved such efficiency in older HDFs substantially. Despite the importance of SIRT6, little is known about the molecular mechanism of its regulation. We show, for the first, time posttranscriptional regulation of SIRT6 by miR-766 and inverse correlation in the expression of this microRNA in HDFs from different age groups. Our results suggest that SIRT6 regulates miR-766 transcription via a feedback regulatory loop, which has implications for the modulation of SIRT6 expression in reprogramming of aging cells.